PENGARUH RASIO KAPITAL-TENAGA KERJA, TINGKAT PENDIDIKAN, STOK KAPITAL DAN PERTUMBUHAN PENDUDUK TERHADAP TINGKAT PERTUMBUHAN GDP INDONESIA - Neni Pancawati (UGM, 2000)
This paper inspirited by Kelley and Schimidt research on Aggregate Population and Economic Growth: The Role of the Components of Demographic Change. According to Kelley and Schmidt, there are three approach to analyze the influence of demographic varables to the economic growth: linear correlation, the production function and the convergence model. Kelley and Schimdt used convergence model and this research used production function model. The results of analyses show that Kelley and Schimidt experience on the difficult to interpret the infulence of demographics variables on the economic growth was real, because there is not direct causation berween both variables. This research found that education level proxies by gross enrollment ration have not influence the rate of uotput (GDP) growth. But it does not mean that there s no impact between education and the rate of output grwoth, because education variable need other variable as a bridge to influence the rate of output growth significantly. Beside that our finding show taht the paraameter of ratio of capital to labor is to high than the parameter ofg the stock capital increases. It mean that the efforts to increases the ratio of capital to labor very important to ensure sustainability of the output growth in the future.